Role of Interventional Radiologist in the Management of Acute Pulmonary Embolism - Bremer, William; Ray, Charles E., Jr.; Shah, Ketan Y. (Seminars in Interventional Radiology, 2020)
Pulmonary embolism is a common cause of morbidity and mortality which continues to increase in overall incidence. Because it can occur with a wide range of clinical presentations, different guidelines have been developed for appropriate risk stratification of patients; interventional radiology plays a vital role in the management of both massive and submassive pulmonary embolism. Catheter-directed therapy, including mechanical and aspiration thrombectomy, standard catheter-directed thrombolysis, and ultrasound-accelerated thrombolysis, has many benefits, including lower thrombolytic doses and intraclot administration of thrombolytic therapy. While the role of catheter-directed therapy is still being developed, four important prospective studies have demonstrated its safety and efficacy. Additional studies comparing short- and long-term clinical outcomes in patients treated with catheter-directed therapy versus anticoagulation are the next step in understanding its role within the management of submassive pulmonary embolism. Furthermore, multidisciplinary pulmonary embolism response teams, in which interventional radiology plays a crucial role, are becoming essential to appropriately managing pulmonary embolism patients, including selection of those who may benefit from catheter-directed therapy.
Keywords: pulmonary embolism; submassive pulmonary embolism; catheter-directed therapy; catheter-directed thrombolysis; pulmonary embolism response team; interventional radiology